Applying the Problem-Based Learning Model to Foster Higher-Order Thinking Skills in Primary Science Classrooms - Muhammad Feri (CV. Yazri Aksara Nusantara, 2025)
The low level of scientific literacy among Indonesian elementary school students remains a major challenge in education, requiring innovative and contextual learning strategies. This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in improving elementary students’ science learning outcomes while enhancing higher-order thinking skills. A quasi-experimental method was employed with a pretest-posttest control group design. The participants consisted of 20 fourth-grade students divided into experimental and control groups. The research instrument was a learning achievement test, and the data were analyzed using an independent t-test to examine differences between the two groups. The findings revealed a significant improvement in the experimental group compared to the control group, both in terms of mean scores and the range of learning outcomes. These results confirm that PBL not only enhances science learning achievement but also positively influences students’ motivation and engagement. This study contributes to the development of constructivist-based teaching practices that align with 21st-century educational demands. Future research is recommended to involve larger samples and longer study durations to explore the long-term impact of PBL on students’ scientific literacy.